2012
DOI: 10.1093/rpd/ncs247
|View full text |Cite
|
Sign up to set email alerts
|

The new VARSKIN 4 photon skin dosimetry model

Abstract: A new photon skin dosimetry model, described here, was developed as the basis for the enhanced VARSKIN 4 thin tissue dosimetry code. The model employs a point-kernel method that accounts for charged particle build-up, photon attenuation and off-axis scatter. Early comparisons of the new model against Monte Carlo particle transport simulations show that VARSKIN 4 is highly accurate for very small sources on the skin surface, although accuracy at shallow depths is compromised for radiation sources that are on cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…Osborne et al (2021) previously reported that for cases of radiopharmaceutical extravasation, deep tissue dose can be significantly higher than dose to overlying skin. Additionally, appropriate tools already exist for the complex task of skin dosimetry (e.g., VARSKIN) (Hamby and Mangini 2018). For these reasons, we chose instead to concentrate only on calculation of tissue absorbed dose.…”
Section: Discussionmentioning
confidence: 99%
“…Osborne et al (2021) previously reported that for cases of radiopharmaceutical extravasation, deep tissue dose can be significantly higher than dose to overlying skin. Additionally, appropriate tools already exist for the complex task of skin dosimetry (e.g., VARSKIN) (Hamby and Mangini 2018). For these reasons, we chose instead to concentrate only on calculation of tissue absorbed dose.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition, density, and dimensions of the Gafchromic layers, 17 as well as for the plastic 5‐cm‐diameter petri and the plastic foil, were also included in the MC simulation. The output dose was recorded in the central 28‐µm active layer of the simulated film.…”
Section: Methodsmentioning
confidence: 99%
“…The MC-based LUT was compared with that obtained using VARSKIN software, 17 reported in literature as a reference tool for brachytherapy using 188 Re resin. 2,4 VARSKIN allows the calculation of the dose at a specified depth, assuming a homogenous activity distribution in several reference geometries.…”
Section: Comparison Between the Mc-based And Varskin Lutmentioning
confidence: 99%
“…Other codes exist to model dose to the skin, including VARSKIN, but are primarily designed for regulatory compliance. VARSKIN in particular was designed to measure dose from dermal contamination and hot particles with respect to a contiguous 10-cm 2 area of skin at a depth of 0.007 cm up to the dose limit of 0.5 Gy 31 . As this work focuses on acute radiation injury to tissue including but not limited to the basal skin layer at potentially extreme doses (>10 Gy in some cases, far exceeding regulatory limits), MCNP5 was used instead.…”
Section: Methodsmentioning
confidence: 99%